Clenbuterol changes phosphorylated FOXO1 localization and decreases protein degradation in the sartorius muscle of neonatal chicks*. Issue 8 (2nd August 2016) - Shimamoto, Saki; Ijiri, Daichi; Nakashima, Kazuki; Kawaguchi, Mana; Ishimaru, Yoshitaka; Furukawa, Airi; Ohtsuka, Akira
Abstract : To investigate the intracellular signaling mechanisms by which clenbuterol reduces muscle protein degradation, we examined the phosphorylation level and intracellular localization of FOXO1 in the sartorius muscle of neonatal chicks. One-day-old chicks were given a single intraperitoneal injection of clenbuterol (0.1 mg/kg body weight). Three hours after injection, AKT protein was phosphorylated in the sartorius muscle by clenbuterol injection. Coincidentally, clenbuterol increased cytosolic level of phosphorylated FOXO1 protein, while it decreased nuclear level of FOXO1 protein in the sartorius muscle. Furthermore, clenbuterol decreased the expression of mRNAs for muscle-specific ubiquitin ligases (atrogin-1/MAFbx and MuRF1) in the sartorius muscle accompanied by decreased plasma 3-methylhistidine concentration, an index of muscle protein degradation, at 3 h after injection. These results suggested that, in the sartorius muscle of the chicks, clenbuterol changed the intracellular localization of phosphorylated FOXO1, and consequently decreased protein degradation via suppressing the expression of genes encoding muscle-specific ubiquitin ligases. Graphical abstract: